Dipotassium disulfanilamidate trihydrate - How, F.N.F.; Ali, Hapipah Mohd; Khaledi, H.; Rahima, Z.A. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, 2K(+)center dot-2C(6)H(7)N(2)O(2)S(-)center dot 3H(2)O, consists of two potassium cations located on mirror planes, one sulfanilamidate anion in a general position and one and a half molecules of water, one of which is also located on a mirror plane. One potassium cation is seven-coordinated by six sulfonyl O atoms and one water molecule, whereas the other is surrounded by six water O atoms and two sulfonyl O atoms. In the crystal structure, the components are connected into polymeric sheets in the bc plane. The two-dimensional structure is consolidated by N-H center dot center dot center dot O, O-H center dot center dot center dot O, O-H center dot center dot center dot N and C-H center dot center dot center dot pi interactions. The layers are further linked into a three-dimensional network via N-H center dot center dot center dot O, N-H center dot center dot center dot N and O-H center dot center dot center dot N hydrogen bonds.